Disability in the Hebrew Bible: interpreting mental and physical differences - Olyan, Saul M. (Cambridge Univ. Press, 2008)
Chapter 1 : Constructions of beauty and ugliness -- Chapter 2 : Physical disabilities classified as "defects" -- Chapter 3 : Physical disabilities not classified as "defects" -- Chapter 4 : Mental disability -- Chapter 5 : Disability in the prophetic utopian vision -- Chapter 6 : Non-somatic parallels to bodily wholeness and "defect" -- Chapter 7 : Exegetical perpetuations, elaborations and transformations : the case of Qumran "defects" in the Dead Sea scrolls